Malignant tumors of the small intestine: A histopathologic study of 41 cases among 1,312 consecutive pecimens of small intestine - Terada, Tadashi (e-Century Publishing Corporation, 2012)
There are few comprehensive studies of small intestinal malignancies. The author retrospectively reviewed 1,312 archival pathologic specimens of the small intestine in the last 10 years in our pathologic laboratory in search for malignant tumors of the small intestine. There were 22 cases (1.7%) of primary adenocarcinoma, 3 cases (0.2%) of primary squamous cell carcinoma, 6 cases (0.5%) of metastatic carcinoma, 6 cases (0.5%) of malignant lymphoma, 3 cases (0.2%) of carcinoid tumor, and 1 case (0.08%) of gastrointestinal stromal tumor (GIST). Of the 25 cases of primary adenocarcinoma and squamous cell carcinoma, 24 cases were located in the duodenum and 1 case in the ileum. The 22 cases of adenocarcinoma were classified into 7 well differentiated, 7 moderately differentiated, and 8 poorly differentiated adenocarcinomas. All the three squamous cell carcinomas were moderately differentiated ones with keratinization and intercellular bridges. In the 25 cases of carcinoma, immunoreactive p53 protein was present in 23 cases, and the Ki-67 labeling ranged from 40% to 95% with a mean of 76%. In the 6 cases of metastatic adenocarcinoma, the origin was ovary in 1 case, pancreas in 2 cases, gall bladder in 1 case, lung in 1 case, and colon in 1 case. In the 6 cases of lymphoma, 4 cases were diffuse large B-cell lymphomas and 2 cases were peripheral T-cell lymphomas. In the 3 cases of carcinoid tumor, all were typical carcinoids and immunohistochemically positive for at least one of neuroendocrine markers (chromogranin, synaptophysin, neuron specific enolase, and CD56). In the 1 case of GIST, the cell type is spindle and GIST cells were immunohistochemically positive for KIT and CD34. The histological risk was intermediate. Forty-one cases of small intestinal malignancies were reviewed histopathologically.